Kesiapan Kerja Mahasiswa Akuntansi di Era Disrupsi Teknologi Digital: Peran Keahlian Akuntansi, Literasi Digital, Literasi Manusia, dan Adaptabilitas Karir - Ratily Pakpahan, Silvia; Nikmah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the era of digital technology disruption, accounting students need to be prepared and have the skills to succeed in the accounting profession. This study aims to examine the impact of accounting skills, digital literacy, human literacy and career adaptability on job readiness. The data source used is primary data collected online through Google forms using the purposive sampling method. The population of this study took a sample of 325 respondents, namely active undergraduate accounting students in the island of Sumatra. The research technique used is the structural equation modelling (SEM) method based on the Partial Least Square (PLS) analysis tool version 4.0. The results indicate that accounting skills variables, digital literacy variables, human literacy variables, and career adaptability variables have a positive and significant influence on job readiness in the era of digital technology disruption. Thus, the results of this study can show that accounting students on the island of Sumatra will be better prepared for their job readiness if supported by the understanding and skills of these students.